Increasing the Brand Awareness of Surabaya’s Coffee Shops in Partnership with Maru Design - Laurencia Citraningrum (Institute of Research and Community Outreach - Petra Christian University, 2021)
Maru Design is Surabaya branding agency for small to medium businesses. During author’s internship, Maru Design wanted a tool to help recognition of local coffee shops in Surabaya. The purpose is to raise brand awareness, so Maru Design get indirect promotion. The solution is creating a coffee shops guidebook consists of reviews by author and designed by Maru Design. Therefore, guidebook can be used to increase brand awareness of local coffee shops while promoting Maru Design. The author conduct an online questionnaire to 30 college students who are coffee shops' visitors and coffee drinkers. Then, observation of the shop and owner's interview to complete the guidebook. Guidebook was made by applying theory of making guidebook by Noor (2018), coffee shop photography by Mike (2017), Writing by Cohen (2017) and Electronic book by Cepulskaite (2020). Through the finding, it is effective because it’s timeless aspect and easy access. Keywords: Brand awareness, Promotion, Guidebook, Coffee shops